Dobór instrumentów formułowania i implementacji strategii: Tool selection for strategy formulation and implementation - Szarucki, Marek (Management and Administration Journal, 2021)
Strategy formulation and implementation constitute a very important methodological aspect in the process of the application of different methods of strategic management. Most available research concentrates only on the description of these instruments. The issue of methods selection is very often omitted and marginalized. The main question is: How to select an appropriate tool in the process of organizational strategy formulation and implementation? The main goal of the paper is to reveal the problem of tool selection for strategy formulation and implementation.